2010
DOI: 10.3136/fstr.16.447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Lipid Type on the Enhancement of Swimming Endurance of Mice by L-Lactic Acid

Abstract: Mice fed either a diet containing 6% lard, fish oil or Erabu sea snake lipids for 16 weeks were intraperitoneally injected L-lactic acid or glucose (25 mg/kg) following injection of physiological saline and subjected to swimming tests at 30 min after each injection. The swimming time ratio of lactic acid to saline injections was greater in mice fed sea snake lipids than those fed lard (p < 0.01) or fish oil (p < 0.05), and significantly greater than that of glucose to saline injections only in mice fed sea sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Individual mice were identified by ear punches. At baseline, the mice had similar body weights and swimming time to exhaustion, as measured by the forced swimming system described in our previous studies [1,2,3,22,23]. The mice were then fed the experimental diets for 12 weeks, and the swimming times were reassessed using the same system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual mice were identified by ear punches. At baseline, the mice had similar body weights and swimming time to exhaustion, as measured by the forced swimming system described in our previous studies [1,2,3,22,23]. The mice were then fed the experimental diets for 12 weeks, and the swimming times were reassessed using the same system.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing evidence suggests that different types of dietary lipids (such as safflower oil, sea-snake oil, conjugated linoleic acid, and medium-chain triglycerides) have varying effects on endurance [1,2,3,4,5,6]. Our previous studies [1,2,3] indicated that n–3 polyunsaturated fatty acids (PUFAs) do not actively improve endurance in mice. This finding has been supported by human studies in which supplementation with n–3 PUFA-rich fish oil failed to increase performance in endurance athletes [7] and well-trained soccer players [8].…”
Section: Introductionmentioning
confidence: 99%